2016
DOI: 10.3791/54533
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Spray Droplet Size from Agricultural Nozzles Using Laser Diffraction

Abstract: When making an application of any crop protection material such as an herbicide or pesticide, the applicator uses a variety of skills and information to make an application so that the material reaches the target site (i.e., plant). Information critical in this process is the droplet size that a particular spray nozzle, spray pressure, and spray solution combination generates, as droplet size greatly influences product efficacy and how the spray moves through the environment. Researchers and product manufactur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…The volumetric droplet diameters and proportion of spray volume contained in droplets with a diameter below 150 µm (% < 150 µm) for the different BFS nozzles under different spray pressures and air velocities are shown in Figures 2-4. Figure 2a shows that the results obtained in this study were similar to those in previous reports [29][30][31], which showed the droplet diameter size decreased with increasing spray pressure. More details were observed in this study as follows: (1) When spray pressure increased from 200 kPa to 300 kPa, Dv0.1, Dv0.5 and Dv0.9 decreased 16.1%, 15.8% and 14.4%, respectively; (2) when spray pressure increased from 300 kPa to 400 kPa, Dv0.1, Dv0.5 and Dv0.9 decreased 14.0%, 15.4% and 13.3%, respectively; (3) when spray pressure increased from 400 kPa to 500 kPa, Dv0.1, Dv0.5 and Dv0.9 decreased 8.6%, 11.2% and 10.4%, respectively; (4) when spray pressure increased from 500 kPa to 600 kPa, Dv0.1, Dv0.5 and Dv0.9 decreased 6.0%, 7.9% and 7.7%, respectively; (5) when spray pressure increased from 600 kPa to 700 kPa, Dv0.1, Dv0.5 and Dv0.9 decreased 2.5%, 3.0% and 2.3%, respectively.…”
Section: Influencesupporting
confidence: 90%
“…The volumetric droplet diameters and proportion of spray volume contained in droplets with a diameter below 150 µm (% < 150 µm) for the different BFS nozzles under different spray pressures and air velocities are shown in Figures 2-4. Figure 2a shows that the results obtained in this study were similar to those in previous reports [29][30][31], which showed the droplet diameter size decreased with increasing spray pressure. More details were observed in this study as follows: (1) When spray pressure increased from 200 kPa to 300 kPa, Dv0.1, Dv0.5 and Dv0.9 decreased 16.1%, 15.8% and 14.4%, respectively; (2) when spray pressure increased from 300 kPa to 400 kPa, Dv0.1, Dv0.5 and Dv0.9 decreased 14.0%, 15.4% and 13.3%, respectively; (3) when spray pressure increased from 400 kPa to 500 kPa, Dv0.1, Dv0.5 and Dv0.9 decreased 8.6%, 11.2% and 10.4%, respectively; (4) when spray pressure increased from 500 kPa to 600 kPa, Dv0.1, Dv0.5 and Dv0.9 decreased 6.0%, 7.9% and 7.7%, respectively; (5) when spray pressure increased from 600 kPa to 700 kPa, Dv0.1, Dv0.5 and Dv0.9 decreased 2.5%, 3.0% and 2.3%, respectively.…”
Section: Influencesupporting
confidence: 90%
“…In the Spraytec equipment, the entire jet crosses the laser beam transversely during the reading. In image-based equipment, if there is no tip or equipment movement structure, there is a focus region that limits the analyzed area (Fritz & Hoffmann, 2016). Thus, in spray tips with a variation of droplet size along the sprayed jet, such as flat fan spray tips, there may be a greater discrepancy between the analyzed spectra.…”
Section: Resultsmentioning
confidence: 99%
“…A nozzle type that produces big droplets size is usually selected to control spray drift. Whereas, the type that mainly produces fine size is utilized to increase spray deposition and spray coverage percentage on the zone treated (11,16). Selection of the correct nozzle critical type and nozzle pressure is the most important issue to reach certainly the effective spray deposition and spray coverage thereby improving pest and weed control (6).…”
Section: Introductionmentioning
confidence: 99%